Dose-dependent effects of lead induced gut injuries: An in vitro and in vivo study. (March 2021) - Yu, Leilei; Yu, Yaqi; Yin, Ruijie; Duan, Hui; Qu, Dingwu; Tian, Fengwei; Narbad, Arjan; Chen, Wei; Zhai, Qixiao
Abstract: Lead (Pb) toxicity has been widely studied, but its dose-dependent toxic effects on the gut remain unclear, therefore, the aim of this study was to evaluate the effects of different doses of Pb exposure on the gut microbiota and gut barrier in vitro and in vivo . The HT-29 cell model was used to determine the Pb-induced effects on cell viability, reactive oxygen species (ROS), and tight junction proteins (TJPs) in vitro, and C57BL/6 mice models exposed to 0, 20, 100, 500, and 1000 mg/kg Pb were used to investigate the Pb-induced dose-dependent effects on the gut microbiota, TJP expression, and colon histopathology. Our results showed that the exposure of HT-29 cells to 8 mM Pb decreased cell viability by 50%, elevated ROS levels by 200%, and suppressed the expression of the TJPs, zonula occludens-1 (ZO-1) and occludin by 23% and 35%, respectively. Consistently, Pb-exposed mice showed significant increases in colon tissue damage and inflammation and reductions in ZO-1 mRNA levels in a dose-dependent manner. The occludin mRNA levels decreased in the 500 and 1000 mg/kg groups. At the genus level, the relative abundance of Coprococcus and Oscillospira decreased and that of Lactobacillus increased in linear manner with the Pb exposure dose. PICRUSt analysis based on 16S rRNA sequencing revealed Pb dose-dependent alterations in metabolism through the gut microbiota. These findings suggest that Pb exposure can not only disrupt the barrier by generating oxidative stress, but can also induce gut dysbiosis, colon tissue damage, and gut inflammation in a dose-dependent manner. Graphical abstract: Image 1 Highlights: Pb-induced gut injuries are related to the disorder of gut microbiota. The Pb-induced colonic damage and inflammation are dose-dependent. Pb reduced ZO-1 expression in a dose-dependent manner. Pb-induced changes in abundance of gut microbiota are dose-dependent.